A Case Study of Prospective Teacher Students' Views on the Position of Mathematics on Human Civilization - Anisyah Pratiwi Putri; Yulyanti Harisman; Wahyu Hidayat; Lukman Harun (Department of Mathematics, Universitas Negeri Padang (UNP), 2022)
In everyday life, mathematics plays an important role, both as a tool, language, mindset, and knowledge, such as numeration systems, currency exchange tools, and so on. Therefore, we should know the role or position of mathematics in human civilization. The selected research is qualitative with a case study method. Two students were selected to be research subjects from five classes in the mathematics education study program. The instrument used in this study was an open interview. Each student is asked questions about their knowledge of the position of mathematics in human civilization. The data analysis used in this research is thematic analysis. The results showed that there were four categories of how mathematics education students responded to the position of mathematics in civilization. The categories are theoretical history student, religious history student, contextual history student, and scientific history student. The four categories will be described in detail in this paper.